State Martyr Representation and Performativity of Political Violence - Scolari, Baldassare (Media and Religion | Medien und Religion, 2019)
The politician Aldo Moro was abducted and killed in 1978 by the terrorist organisation the Red Brigades. The media then stylised Moro as a 'state martyr'. This volume deals with the highly topical question concerning the performativity of this concept in the tension between democratic states and terrorism and reconstructs a crucial phase of post-war policy in Italy on the basis of media sources on the Moro case. What role does a term from Christian antiquity play within modern sociopolitical discourses? What changes has the term 'martyr' undergone in European religious and cultural history? On the basis of these questions, this study opens up an interdisciplinary theoretical horizon in order to understand the role of religious motifs in sociopolitical contexts. It brings a central new dimension to the secularisation debate, which sees secularisation as a new configuration of politics and religion.